Transmetallation from CCC-NHC pincer Zr complexes in the synthesis of air-stable CCC-NHC pincer Co(iii) complexes and initial hydroboration trials. Issue 7 (27th January 2016) - Reilly, Sean W.; Webster, Charles Edwin; Hollis, T. Keith; Valle, Henry U.
Abstract : Transmetallation from an isolated CCC-NHC Zr complex efficiently produces the Co complex, which catalyzes hydroboration. Abstract : Development of CCC-NHC pincer Co complexes via transmetalation from Zr is reported. Formation of these air-stable Co(iii ) complexes was achieved through use of a CoCl2 or Co(acac)3 in situ or with a discrete CCC-NHC pincer Zr transmetallating agent. Preliminary activity in the hydroboration of styrene is reported. This facile methodology will further the development of CCC-NHC pincer first-row transition metal complexes.